S-nitrosylation of the thioredoxin-like domains of protein disulfide isomerase and its role in neurodegenerative conditions - Conway, Myra E.; Harris, Matthew (Frontiers in Chemistry, 2015)
Correct protein folding and inhibition of protein aggregation is facilitated by a cellular ‘quality control system’ that engages a network of protein interactions including molecular chaperones and the ubiquitin proteasome system. Key chaperones involved in these regulatory mechanisms are the protein disulphide isomerases (PDI) and their homologues, predominantly expressed in the endoplasmic reticulum of most tissues. Redox changes that disrupt ER homeostasis can lead to modification of these enzymes or chaperones with the loss of their proposed neuroprotective role resulting in an increase in protein misfolding. Misfolded protein aggregates have been observed in several disease states and are considered to play a pivotal role in the pathogenesis of neurodegenerative conditions such as Alzheimer’s disease, Parkinson’s disease, and Amyotrophic Lateral sclerosis. This review will focus on the importance of the thioredoxin-like –CGHC- active site of PDI and how our understanding of this structural motif will play a key role in unravelling the pathogenic mechanisms that underpin these neurodegenerative conditions.